Technology and Indonesia's Industrial Competitiveness - Thee Kian Wie (Asian Development Bank Institute (ADBI), 2006)
This paper will discuss the major factors, which affect Indonesia's industrial competitiveness, specifically the determinants of its industrial technology development, which is crucial to raising Indonesia's competitiveness. After a brief overview of industrial development before and after the Asian economic crisis, the paper discusses some recent assessments of the country's competitiveness. It considers the determinants of Indonesia's industrial technological development, including policy options open to the government. The author recommends that as Indonesia's technology support services, specifically the public MSTQ services, have in general not performed adequately in meeting the needs of firms, privatizing these services would be advisable. This will not only lessen the fiscal burden, but more important, it will enable these important services to aim their services specifically at the needs of private industry. These efforts, however, will only be successful if the government also manages to eliminate the various factors, which currently account for the poor investment climate which, in turn, imposes high costs on firms which reduces their competitiveness relative to firms in the other East Asian countries.
hdl:11540/4177
Keywords: 330